2021
DOI: 10.7575/aiac.ijkss.v.9n.4p.21
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Futsal Coach Competency Evaluation Instruments

Abstract: Background: The study of the futsal coach competency evaluation instrument was done because there was no any existed instrument used to measure the futsal coach competence. Objective: This research aims to determine the validity and reliability of the futsal coach competency evaluation instrument. Method: the validation and reliability instruments were determined using three quantitative methods in the main phases or steps, which are expertly judged (content validation), theory test (logical validation) and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These results were reinforced by Bahari, Hanief, & Junaedi (2020) in their research that futsal extracurriculars were in the moderate category. Furthermore, research conducted on health students showed less (Maliqi et al, 2022), and also Physical Education students (Panchuk et al, 2022), as well as highland junior high school students (Firmansyah et al, 2021). Phys.…”
Section: Discussionmentioning
confidence: 99%
“…These results were reinforced by Bahari, Hanief, & Junaedi (2020) in their research that futsal extracurriculars were in the moderate category. Furthermore, research conducted on health students showed less (Maliqi et al, 2022), and also Physical Education students (Panchuk et al, 2022), as well as highland junior high school students (Firmansyah et al, 2021). Phys.…”
Section: Discussionmentioning
confidence: 99%
“…This process entails analyzing whether current implementations align with the long-term needs of sports development in Papua or require adjustments. Policy analysis serves as an evaluation tool, measuring the success level of policies (Firmansyah et al, 2021). In cases where existing policies prove ineffective, reviews and recommendations from diverse policy literature studies are conducted and adopted.…”
Section: Introductionmentioning
confidence: 99%
“…This situation results in the quality of learning in schools needing to be more effective and the standard of infrastructure in schools being neglected (Irfan et al, 2020). A teacher's educational background determines how the learning process takes place (Amalia et al, 2021) and whether the quality taught is relevant to the applicable material and curriculum (Firmansyah et al, 2021). This kind of problem still occurs in areas that still need a lot of physical education teachers, especially at the elementary school level (Arisetya Purwadi et al, 2022).…”
mentioning
confidence: 99%